2014
DOI: 10.1172/jci73615
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic TRAP80 selectively regulates lipogenic activity of liver X receptor

Abstract: Supernatants obtained from each step were stored at -70°C. For the infection of mice and mouse primary hepatocytes, Ad-293 cells were infected with crude stock virus, lysed by freezing and thawing after 24 to 48 hours, and the viruses were purified using CsCl 2 gradients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…One recent study suggested that the hepatic LXR lipogenic program might be separated from cholesterol efflux. Silencing the LXR co-activator TRAP80 was reported to interfere with LXR-mediated induction of Srebpf1 but not Abca1 146 . However, the robust expression of Abca1 by Küpffer cells complicates the interpretation of these results.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study suggested that the hepatic LXR lipogenic program might be separated from cholesterol efflux. Silencing the LXR co-activator TRAP80 was reported to interfere with LXR-mediated induction of Srebpf1 but not Abca1 146 . However, the robust expression of Abca1 by Küpffer cells complicates the interpretation of these results.…”
Section: Introductionmentioning
confidence: 99%
“…TRAP80 was previously identified as an LXRa-interacting protein using HepG2 nuclear extracts with GST-LXRa LBD as bait (25). TRAP80 can stimulate the transcription of lipogenic genes, including SREBP-1c, but does not affect the transcription of RCT-related genes, such as ABCA1 (25).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, TRAP80 was reported to be a lipogenic coactivator in hepatocytes (25). TRAP80 is selectively recruited to the SREBP-1c promoter, but not the ABCA1 promoter.…”
Section: Recruitment Of the Coactivator Trap80 To The Srebp-1c Promotmentioning
confidence: 99%
“…Based on these studies, activation of LXRs represents an interesting therapeutic option for neurodegenerative and neuroinflammatory disorders, such as AD. However, synthetic LXR agonists show severe side-effects such as hepatic hypertriglyceridemia, resulting in liver steatosis [147]. By using cell-free and cell-based assays, multiple studies defined that plant sterols, such as sitosterol, fucosterol, stigmasterol, schottenol, 24(S)-saringosterol, and spinasterol, bind and activate LXRa and/or LXRb [46,53,[148][149][150][151].…”
Section: Phytosterols In Alzheimer's Diseasementioning
confidence: 99%